Helical water chain mediated proton conductivity in homochiral metal-organic frameworks with unprecedented zeolitic unh-topology - Sahoo, Subash Chandra; Kundu, Tanay; Banerjee, Rahul (Journal of the American Chemical Society, 2011)
Four new homochiral metal-organic framework (MOF) isomers, [Zn(l-L-Cl)(Cl)](H2O)(2) (1), [Zn(l-L-Br)(Br)]-(H2O)(2) (2), [Zn(d-L-Cl)(Cl)(H2O)(2) (3), and [Zn(d-L-Br)-(Br)] (H2O)(2) (4) [L = 3-methyl-2-(pyridin-4-ylmethylamino)-butanoic acid], have been synthesized by using a derivative of L-/D-valine and Zn(CH3COO)(2)center dot 2H(2)O. A three-periodic lattice with a parallel ID helical channel was formed along the crystallographic c-axis. Molecular rearrangement results in an unprecedented zeolitic unh-toparigy in 1-4. In each case, two lattice water molecules (one H-bonded. to halogen atoms) form a secondary helical continuous water chain inside the molecular helix. MOFs 1 and 2 shows different water adsorption properties and hence different water affinity. The arrangement of water molecules inside the channel Was monitored by variable temperature single crystal X-ray diffraction, which indicated that MOF 1 has a higher water holding capacity than MOF 2. In MOF 1, water escapes. at 80 degrees C, while in T the same happens at a much lower temperature (similar to 40 degrees C). All the MOFs reported here shows reversible crystallization by readily reabsorbing moisture. In MOFs 1 and 2, the frameworks are stable after solvent removal, which is confirmed by a single-crystal to single crystal transformation. MOFs 1 and 3 show high proton conductivity of 4.45 x 10(-5) and 4.42 x 10(-5) S cm(-1), respectively, while 2 and 4 shows zero proton conductivity. The above result is attributed to the fact that MOF 1 has a higher water holding capacity than MOF 2.

Alkali earth metal (Ca, Sr, Ba) based thermostable metal-organic frameworks (MOFs) for proton conduction - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Chemical Communications, 2012)
{Three new alkaline earth metal based MOFs have been synthesized by using 4,4'-sulfobisbenzoic acid (SBBA) and alkaline earth metal salts M(NO3)(2)

Correlation between coordinated water content and proton conductivity in Ca-BTC-based metal-organic frameworks - Mallick, Arijit; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
Proton conductivity of five Ca-based MOFs which depends on the amount of water molecules coordinated to the Ca-centres has been reported. These MOFs show high temperature proton conductivity due to the strong hydrogen bonding between the lattice and coordinated water molecules.

Rapid microwave synthesis of fluorescent hydrophobic carbon dots - Mitra, Shouvik; Chandra, Sourov; Kundu, Tanay; Banerjee, Rahul; Pramanik, Panchanan; Goswami, Arunava (RSC Advances, 2012)
Fluorescent hydrophobic carbon dots (HCDs) have been fabricated from a poloxamer by a simple microwave assisted process within a few minutes for the first time. Small and distinct spherical HCDs emitted bright blue and green fluorescent light depending upon the excitation wavelength and were dispersed easily in a wide variety of organic solvents. HCDs exhibited excellent water resistant behavior with a contact angle of similar to 122 degrees enforcing good hydrophobic character which will be quite useful in potential surface applications.

Reversible phase transformation in proton conducting strandberg-type POM based metal organic material - Dey, Chandan; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
A Cu(II)-phenanthroline connected Strandberg-type polyoxometalate based proton conducting MOF, Cu3Mo5P2, that contains one dimensional parallel water channels has been reported. Cu3Mo5P2 shows proton conduction at room temperature as well as elevated temperature.

Self-assembled one dimensional functionalized metal-organic nanotubes (MONTs) for proton conduction - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
Two self-assembled isostructural functionalized metal-organic nanotubes have been synthesized using 5-triazole isophthalic acid (5-TIA) with In(III) and Cd(II). In-and Cd-5TIA possess one-dimensional (1D) nanotubular architecture and show proton conductivity along regular 1D channels, measured as 5.35 x 10(-5) and 3.61 x 10(-3) S cm(-1) respectively.

Solid-state thermolysis of anion induced metal-organic frameworks to ZnO microparticles with predefined morphologies: facile synthesis and solar cell studies - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Crystal Growth & Design, 2012)
Simple one-step solid state thermolysis of two Zn-based homochiral metal organic frameworks (MOFs) leads to a dramatic difference in morphologies which depends on the anion (-Cl and -Br) and calcination environment (air and N-2). Rod-shaped (aspect ratio similar to 20), hexagonal column shaped (aspect ratio similar to 3), and elliptical aggregation of ZnO morphologies (aspect ratio similar to 3) are obtained and characterized. Although these two MOFs possess similar rod-shaped morphology, they produce dramatic change in resulting ZnO microparticle morphologies (from rod-shaped ZnO microparticles in the case of thermolysis of MOP 1 to hexagonal column shaped ZnO microparticles in the case of MOF 2 thermolysis) when calcined in N-2 at 800 degrees C. However, when we calcined both MOF 1 and 2 in air, we encountered similar elliptical aggregation of ZnO microparticles. These ZnO microparticles show permanent porosity, visible light emission centered at 605 or 510 nm. Moreover, they show 0.15% and 0.14% dye sensitized solar cell activity. To the best of our knowledge, this is the first report of dye sensitized solar cell activity of ZnO microparticles obtained from one-step thermolysis of porous homochiral MOFs.

Variable water adsorption in amino acid derivative based homochiral metal organic frameworks - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Crystal Growth & Design, 2012)
{Six new Cd-containing homochiral metal organic framework materials [

Relating pore hydrophilicity with vapour adsorption capacity in a series of amino acid based metal organic frameworks - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (CrystEngComm, 2013)
A new Zn based porous homochiral metal-organic framework, ThrZnOAc, belonging to unh topology, has been synthesized using pyridyl functionalized threonine and Zn(OAc)(2) as the metal precursor. Stepwise substitution of the homochiral MOF backbone by simply changing the sidearm of the amino acids (isopropyl in the case of valine, methyl in alanine and hydroxyethyl in threonine) resulted in increased water adsorption in ThrZnOAc compared to the previously reported ValZnOAc/AlaZnOAc. Extensive solvent sorption isotherms (water, methanol, isopropanol and toluene) have been carried out, which revealed high solvophilic interaction with polar solvents in ThrZnOAc due to the polar pore [2-hydroxyethyl {-CH(OH)CH3} sidearm of the amino acid], which is not prominent in the corresponding valine/alanine counterparts. The aforementioned functionalization in a series of isostructural amino acid based MOFs with the only difference being in the sidearm and their emergence as enhanced solvophilic materials is unprecedented in the MOF literature.

Salt metathesis in three dimensional metal-organic frameworks (MOFs) with unprecedented hydrolytic regenerability - Kundu, Tanay; Sahoo, Subash Chandra; Saha, Subhadeep; Banerjee, Rahul (Chemical Communications, 2013)
{Eight Zn-based porous (1.2 nm) homochiral MOFs (ValZnX, AlaZnX

Structural isomerism leading to variable proton conductivity in indium(III) isophthalic acid based frameworks - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2013)
Proton conductivity has been studied thoroughly in two isomeric In(III)-isophthalate based MOFs. In-IA-2D-1 is capable of showing proton conductivity (3.4 x 10(-3) S cm(-1)) under humidified conditions (98% RH), whereas In-IA-2D-2 can conduct protons (2.6 x 10(-5) S cm(-1)) under humidified as well as anhydrous conditions.

Amino acid-based multiresponsive low-molecular weight metallohydrogels with load-bearing and rapid self-healing abilities - Saha, Subhadeep; Bachl, Jurgen; Kundu, Tanay; Diaz, David Diaz; Banerjee, Rahul (Chemical Communications, 2014)
A multiresponsive metallohydrogel based on an amino acid-derived low molecular weight (LMW) ligand and a Zn(II) salt was prepared. This hydrogel showed remarkable shape-persistent, self-standing, load-bearing and self-healing properties, which is uncommon in LMW hydrogels.

Crystalline metal-organic frameworks (MOFs): synthesis, structure and function - Dey, Chandan; Kundu, Tanay; Biswal, Bishnu P.; Mallick, Arijit; Banerjee, Rahul (Acta Crystallographica Section B-Structural Science, 2014)
Metal-organic frameworks (MOFs) are a class of hybrid network supramolecular solid materials comprised of organized organic linkers and metal cations. They can display enormously high surface areas with tunable pore size and functionality, and can be used as hosts for a range of guest molecules. Since their discovery, MOFs have experienced widespread exploration for their applications in gas storage, drug delivery and sensing. This article covers general and modern synthetic strategies to prepare MOFs, and discusses their structural diversity and properties with respect to application perspectives.

Dissolvable metallohydrogels for controlled release: evidence of a kinetic supramolecular gel phase intermediate - Saha, Subhadeep; Bachl, Jurgen; Kundu, Tanay; Diaz, David Diaz; Banerjee, Rahul (Chemical Communications, 2014)
Two metallohydrogels based on an amino acid-based ligand and Zn(II) salts were synthesized. These hydrogels show an uncommon, reversible, time-dependent transformation from the opaque to transparent state. These hydrogels also exhibit gradual dissolution in water (pH <= 7) over time. A water-soluble stimulant, caffeine, could be in situ loaded into the hydrogels and slowly released during dissolution.

Ferromagnetic tetranuclear Cu(II) complex: catecholase and phenoxazinone synthase activities - Mitra, Merry; Kundu, Tanay; Kaur, Gurpreet; Sharma, Gyaneswar; Choudhury, Angshuman Roy; Singh, Yogesh; Ghosh, Rajarshi (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: catalysis; Ferromagnetic; Tetranuclear copper

Mechanical downsizing of a gadolinium(iii)-based metal-organic framework for anticancer drug delivery - Kundu, Tanay; Mitra, Shouvik; Patra, Prasun; Goswami, Arunava; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2014)
A Gd-III-based porous metal-organic framework (MOF), Gd-pDBI, has been synthesized using fluorescent linker pDBI (pDBI=(1,4-bis(5-carboxy-1H-benzimidazole-2-yl)benzene)), resulting in a three-dimensional interpenetrated structure with a one-dimensional open channel (1.9x1.2nm) filled with hydrogen-bonded water assemblies. Gd-pDBI exhibits high thermal stability, porosity, excellent water stability, along with organic-solvent and mild acid and base stability with retention of crystallinity. Gd-pDBI was transformed to the nanoscale regime (ca. 140nm) by mechanical grinding to yield MG-Gd-pDBI with excellent water dispersibility (>90min), maintaining its porosity and crystallinity. In vitro and in vivo studies on MG-Gd-pDBI revealed its low blood toxicity and highest drug loading (12wt%) of anticancer drug doxorubicin in MOFs reported to date with pH-responsive cancer-cell-specific drug release.
Keywords: ball-milling; doxorubicin; drug delivery; metal-organic frameworks; nanocarriers

Phosphoric acid loaded azo (-N=N-) based covalent organic framework for proton conduction - Chandra, Suman; Kundu, Tanay; Kandambeth, Sharath; BabaRao, Ravichandar; Marathe, Yogesh N.; Kunjir, Shrikant M.; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Two new chemically stable functional crystalline covalent organic frameworkds (COFs) (Tp-Azo and Tp-Stb) were synthesized using the Schiff base reaction between triformylphloroglucinol (Tp) and 4,4'-azodianiline (Azo) or 4,4'-diaminostilbene (Stb), respectively. Both COFs show the expected keto-enamine form, and high stability toward boiling water, strong acidic, and basic media. H3PO4 doping in Tp-Azo leads to immobilization of the acid within the porous framework, which facilitates proton conduction in both the hydrous (sigma = 9.9 X 10(-4) S cm(-1)) and anhydrous state (sigma = 6.7 X 10(-5) S cm-1). This report constitutes the first emergence of COFs as proton conducting materials.

Structural diversity in serine derived homochiral metal organic frameworks - Kundu, Tanay; Banerjee, Rahul (Journal of Chemical Sciences, 2014)
Two new Zn(II) and Cd(II) based homochiral metal-organic frameworks (MOFs) [SerCdOAc and Zn(Ser)(2)] have been synthesized using pyridyl functionalized amino acid, viz., serine, as an organic linker. The SerCdOAc structure is three dimensional, while that of the Zn(Ser)(2) is two dimensional. The polar voids of the corresponding MOFs are filled with solvent molecules (water in the case of SerCdOAc and methanol in the case of Zn(Ser)(2)). In both cases, metal centres, i.e., Zn(II) and Cd(II), are hexacoordinated. However, with a change in the solvent for synthesis, ligand coordination mode and incorporation of additional coordinated anion resulted in a great change in the final MOF architecture. Herein, for the first time, we could achieve structural variety and synthesize MOFs composed of only metal ion and pyridyl functionalized amino acid linker.
Keywords: Amino acid; crystal engineering; hydrogen bonding; metal organic framework

One-dimensional water cages with repeat units of (H2O)(24) resembling pagodane trapped in a 3D coordination polymer: proton conduction and tunable luminescence emission by adsorption of anionic dyes - Maity, Kartik; Kundu, Tanay; Banerjee, Rahul; Biradha, Kumar (Crystengcomm, 2015)
A 3D-coordination polymer was shown to trap one-dimensional polyhedral water cages consisting of repeat units of (H2O)(24), the geometry of which resembles the exotic organic molecule pagodane. Further, this material exhibited proton conduction ability and tunable luminescence emission by adsorption of anionic dyes such as the fluorescein dianion.

Phosphate enriched polyoxometalate based ionic salts for proton conduction - Dey, Chandan; Kundu, Tanay; Aiyappa, Harshitha Barike; Banerjee, Rahul (RSC Advances, 2015)
A series of [NiMo12O30(PO4)(8)](n-) POM anion and organic cation based ionic composites have been prepared in hydrothermal conditions. The ionic composites with protonated ethylene diamine molecules have been tested for proton conductivity.

Catecholase and phenoxazinone synthase activities of a ferromagnetically coupled tetranuclear Cu(II) complex - Mitra, Merry; Kundu, Tanay; Kaur, Gurpreet; Sharma, Gyaneswar; Choudhury, Angshuman Roy; Singh, Yogesh; Ghosh, Rajarshi (RSC Advances, 2016)
A crystallographically characterized tetranuclear Cu(II) complex [Cu-4(II)(L)(4)] (1) [H2L = N-(2-hydroxyethyl)-3-methoxysalicylaldimine] is found to show overall ferromagnetic exchange coupling. Complex (1) mimics the catalytic activity of the plant enzyme catechol oxidase by oxidising 3,5-di-tert-butylcatechol to its corresponding quinone in methanol and dichloromethane medium in the presence of aerial oxygen. The reaction follows Michaelis-Menten enzymatic reaction kinetics with turnover numbers (K-cat) 6.99 x 10(3) and 1.85 x 10(3) h(-1) in methanol and dichloromethane, respectively. 1 is also phenoxazinone synthase active in methanol medium with a turnover number of 1.21 x 10(5) h(-1).

Gadolinium(III)-based porous luminescent metal-organic frameworks for bimodal imaging - Kundu, Tanay; Mitra, Shouvik; Diaz Diaz, David; Banerjee, Rahul (Chempluschem, 2016)
Gd-III-based metal-organic frameworks, Gd-pDBI-1 and Gd-pDBI-2, have been synthesized using the linker pDBI (pDBI=1,4-bis(5-carboxy-1H-benzimidazole-2yl)benzene). They exhibited structural diversity due to subtle change in reaction constituents. Owing to the judicious choice of the fluorescent linker, the materials could be used for bimodal imaging (fluorescent and magnetic resonance) and displayed a modest T1 relaxivity value.

Interplaying intrinsic and extrinsic proton conductivities in covalent organic frameworks - Chandra, Suman; Kundu, Tanay; Dey, Kaushik; Addicoat, Matthew A.; Heine, Thomas; Banerjee, Rahul (Chemistry of Materials, 2016)
A sulfonic-acid-based covalent organic framework (TpPa-SO3H) has been synthesized that exhibits intrinsic proton conductivity under anhydrous conditions. The sulfonic acid groups are aligned on the two-dimensional (2D) layers at periodic intervals and promote the proton hopping inside the hexagonal one-dimensional channel. The intrinsic proton conductivity of TpPa-SO3H was measured as 1.7 X 10(-5) S cm(-1) at 120 degrees C under anhydrous conditions. To enhance the proton conductivity, we have synthesized a hybrid COF TpPa(SO3H-Py) by a ligand-based solid-solution approach that contains sulfonic acid as the acidic site, as well as pyridine as the basic site, in order to immobilize acidic proton carrier molecules. Impregnation of phytic acid molecules inside the framework increases the anhydrous proton conductivity up to 5 x 10(-4) S cm(-1) at 120 degrees C. Such an approach highlights the advantage and first-time use of hybrid COF for interplaying intrinsic to extrinsic proton conductivity.

Mechanochemically synthesized covalent organic framework as a proton-conducting solid electrolyte - Shinde, Digambar Balaji; Aiyappa, Harshitha Barike; Bhadra, Mohitosh; Biswal, Bishnu P.; Wadge, Pritish; Kandambeth, Sharath; Garai, Bikash; Kundu, Tanay; Kurungot, Sreekumar; Banerjee, Rahul (Journal of Materials Chemistry A, 2016)
Mechanochemistry has become an increasingly important synthetic tool for a waste-free environment. However, the poor quality of the so-derived materials in terms of their crystallinity and porosity has been their major drawback for any practical applications. In this report, we have for the first time successfully leveraged such characteristics to show that the mechanochemically synthesized bipyridine based covalent organic framework (COF) outperforms its conventional solvothermal counterpart as an efficient solid-state electrolyte in PEM fuel cells. Marking the first such attempt in COFs, a Membrane Electrode Assembly (MEA) fabricated using the mechanochemically synthesized COF was observed to inhibit the fuel crossover and build up a stable Open Circuit Voltage (OCV = 0.93 V at 50 degrees C), thereby establishing itself as an effective solid electrolyte material (with a proton conductivity of 1.4 x 10(-2) S cm(-1)), while the solvothermally synthesized COF proved ineffective under similar conditions.

Targeted drug delivery in covalent organic nanosheets (CONs) via sequential postsynthetic modification - Mitra, Shouvik; Sasmal, Himadri Sekhar; Kundu, Tanay; Kandambeth, Sharath; Math, Kavya; Diaz Diaz, David; Banerjee, Rahul (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as a new class of functional two-dimensional (2D) porous organic polymeric materials with a high accessible surface, diverse functionality, and chemical stability. They could become versatile candidates for targeted drug delivery. Despite their many advantages, there are limitations to their use for target specific drug delivery. We anticipated that these drawbacks could be overturned by judicious postsynthetic modification steps to use CONs for targeted drug delivery. The postsynthetic modification would not only produce the desired functionality, it would also help to exfoliate to CONs as well. In order to meet this requirement, we have developed a facile, salt-mediated synthesis of covalent organic frameworks (COFs) in the presence of p-toluenesulfonic acid (PTSA). The COFs were subjected to sequential postsynthetic modifications to yield functionalized targeted CONs for targeted delivery of 5-fluorouracil to breast cancer cells. This postsynthetic modification resulted in simultaneous chemical delamination and functionalization to targeted CONs. Targeted CONs showed sustained release of the drug to the cancer cells through receptor mediated endocytosis, which led to cancer cell death via apoptosis. Considering the easy and facile COF synthesis, functionality based postsynthetic modifications, and chemical delamination to CONs for potential advantageous targeted drug delivery, this process can have a significant impact in biomedical applications.